Particle Sizes Effect of Application Forage Processing Technology on Consumption Efficiency, Palatability and Digestibility of Local Goat - Iswarin, Retno; Fani, Furiska; Pambudi, Andre Wira (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
Livestocks digestible feed ability is affected by the physical and chemical quality of the feed given. Study feed processing application on a local goat feed particle size needs to be done for efficiency of feeding patterns. This study aimed to evaluate the best forage particle size on efficiency consumption, palatability and digestibility of the local goat. The experimental method was done with randomized completely block design with 3x2x3 factorial. Goats are grouped by weight, the first factor is the form of feed (fresh, dried) with particle feed size of 3 - 5 - > 7 cm as the second factor. The results showed that particle size of > 7 cm gives the optimal feed consumption and palatability. Dry and organic materials digestibility provided the best on the particle size of 3 cm. Forms of dry feed has a positive correlation with consumption, palatability and digestibility of feed. Conclusion of the study recommended dried forage given to the local goats with a particle size of 3 cm is able to provide efficiency in consumption and palatability of the feed with the most excellent digestibility.Â